Workshop on Large Scale Implementation of the Alternate Wetting and Drying (AWD) Technology - International Rice Research Institute (2019)
The report documents the Workshop on Large Scale Implementation of the Alternate Wetting and Drying (AWD) Technology organized by the International Rice Research Institute on May 4, 2019 in Dhaka, Bangaldesh. The workshop aimed to: share experiences in AWD dissemination of Focal Area Network (FAN) members with other research and development organizations, as well as with policy makers; explore opportunities to establish other networks similar to FAN in other regions of Bangladesh that can take on the dissemination of water-saving techniques; and identify future funding options for implementing climate-smart and low-emissions technologies in accordance with national plans.